1966
DOI: 10.1172/jci105476
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of testoterone and related steroids in metastatic interstitial cell carcinoma of the testis.

Abstract: Interstitial cell carcinoma of the testis is a singularly rare steroid-producing cancer. Of the seven reported cases (1-7), urinary 17-ketosteroid (17-KS) excretion was high in the four cases in which it was measured. Abelson, Bulaschenko, Trommer, and Valdes-Dapena (7) fractionated the urinary 17-ketosteriods and corticoids in one recently reported case. There is, however, no comprehensive study of either the production of androgens or related steroids by this tumor. (testosterone) ; 17a-hydroxy-androst-4-en-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the scientific literature investigated, besides urinary metabolites related to many cancer forms, also specific biomarkers, such as sarcosine for prostate cancer [57,58,59,61,63,64,65], NGAL, MMP-9 and ADAM 12 for breast cancer [44,45], HCG for testicular cancer [133,134], h.KIM-1 for renal cancer [126] or Prostaglandin E2 for gastric cancer [82] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature investigated, besides urinary metabolites related to many cancer forms, also specific biomarkers, such as sarcosine for prostate cancer [57,58,59,61,63,64,65], NGAL, MMP-9 and ADAM 12 for breast cancer [44,45], HCG for testicular cancer [133,134], h.KIM-1 for renal cancer [126] or Prostaglandin E2 for gastric cancer [82] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A quite remarkable feature of the steroid composition of human testis tissue is the presence of a number of sulfateconjugated Q9 and C2i steroids. It has already been demonstrated that boar testis secretes dehydroepiandrosterone sulfate (Baulieu et al, 1967), that testis with interstitial cell carcinoma secretes the same conjugate (Lipsett et al, 1966) and that normal human testis secretes testosterone, pregnenolone, and possibly 5-androstene-3/3,17/3-diol sulfates (Laatikainen et al, 1969). Upon stimulation with HCG considerable secretion of dehydroepiandrosterone, 5-androstene-3/3,17/3-diol, and pregnenolone sulfates was observed, but no increase in the secretion of testosterone sulfate (Laatikainen et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of these urinary 17-ketosteroids not only gave an indication of adrenal function, but also of its maturity (Brooks, 1975;Gupta, 1975). Similarly, patients with adrenal tumours have one or more highly elevated amounts of steroid present in their urine (Stewart et al, 1936;Lipsett et al, 1966;Root et at., 1972;Holcombe et al, 1983;Watanobe et al, 1985). However, measurement of total 17-ketosteroids does not indicate whether one or a combination of the above mentioned compounds are present in the urine.…”
Section: Discussionmentioning
confidence: 99%